The Role of Information and Communication Technology in Enhancing Instructional Effectiveness in Teachers’ Education in Nigeria. - Asubiojo, Raphael Ojo; Ajayi, James Adedeji (NIU Journal of Social Sciences, 2017)
Information and Communication Technology (ICT) have been recognized as an important tool for advancement of any nation especially in the era of globalization. This has led to the inclusion of ICT education into the National Policy on Education (NPE 2004) of which the Nigerian Tertiary education is one of the beneficiary. Tertiary education is approaching the point at which, science and technology particularly Information and Communication Technology (ICT) will be playing vital roles in nearly all phases of the educational process. This paper takes a look at the roles of ICT in Teachers’ Education in Nigeria toward ensuring instructional effectiveness. ICT provides opportunities for teacher’s professional development, transform teaching, provide network opportunities for teachers and enhance the quality of students learning amongst others. However the paper identifies some of the problems toward the effective use of ICTs in teachers’ education programme in Nigeria to include poor funding, poor power supply, low level of technical education and inadequate supply of ICTs facilities.   Finally, it recommended that government and all the stakeholders in the educational system should wake up to their responsibilities by providing ICTs facilities for effective instructional delivery system in teacher education in Nigeria. Keywords: Education, Pre-Service Teacher, Teacher Education and ICT.